Characteristic Imaging Patterns of Muscle Involvement in Polyarteritis Nodosa: Case Report and Review of the Literature - Huang, Peikai; Liu, Hailong; Zhang, Meng; Chen, Yanxia; Ye, Jingzhi; Liu, Jingfeng; Chen, Jun; Xiao, Meng qiang (Asian Pacific Journal of Cancer Care, 2021)
Objective: Polyarteritis nodosa (PAN) is a rare disease with complex clinical manifestations that are difficult to diagnose. Imaging diagnoses of previously reported patients have focused on vascular manifestations. Magnetic resonance imaging (MRI) has been used to detect muscle involvement in PAN. Here, we reviewed imaging findings pertaining to muscle involvement in patients with PAN. Methods: Twelve articles concerning muscle involvement in PAN were published during the period 1980–2020; 21 patients, including our patient, were examined in this study. Results: Across the published articles, the male to female ratio was 1:1, the mean patient age was 40.76 ± 18.28 years, and there were 17 patients with calf involvement and 3 with thigh involvement. The T1WI and T2WI findings were both isointense in one patient, and the T1WI findings alone were isointense in seven patients. The T1WI findings were slightly hyperintense in five patients, and no T1WI images were available for the remaining seven patients. The T2WI signal was diffusely hyperintense in 10 patients, and “patchy villous hyperintense” in 9 patients. Among the 12 patients with enhanced images, most exhibited diffuse or cotton-like enhancement, while some showed involvement of the fascia and periosteum. The comprehensive imaging analysis of our patient included muscle and blood vessel MRI and computed tomography (CT) examinations. Our patient’s disease involved the calves and thighs, with T1WI isointensity and T2WI patch-like hyperintensity, as well as cotton-like enhancement centered on blood vessels. Computed tomography angiography (CTA) and magnetic resonance angiography (MRA) examinations of the lower limbs showed beadlike changes in the arterial branches, and the lower leg arterial branches were obvious. Head MRA revealed stenosis and occlusion of the right middle cerebral artery. Additionally, the superior mesenteric artery was locally dilated around a tumor, with the greatest width being approximately 9 mm. Cerebral perfusion analysis indicated cerebral blood flow (CBF) was lower in the right cerebellar hemisphere. Conclusions: PAN should be considered in the presence of patchiness or diffuse muscle signal changes on MRI of the lower leg (or thigh), followed by vessel-centered cotton-like enhancement accompanied by fascial or periosteal enhancement. Our findings suggest that systemic examination of small and medium arteries in patients with PAN can aid early prevention and treatment.